Genomic Selection for Grain Yield in the CIMMYT Wheat Breeding Program—Status and Perspectives - Juliana, Philomin; Singh, Ravi Prakash; Braun, Hans-Joachim; Huerta-Espino, Julio; Crespo-Herrera, Leonardo; Govindan, Velu; Mondal, Suchismita; Poland, Jesse; Shrestha, Sandesh (Frontiers in Plant Science, 2020)
Genomic breeding technologies offer new opportunities for grain yield (GY) improvement in common wheat. In this study, we have evaluated the potential of genomic selection (GS) in breeding for GY in wheat by modeling a large dataset of 48,562 GY observations from the International Maize and Wheat Improvement Center (CIMMYT), including 36 yield trials evaluated between 2012 and 2019 in ObregonObregón, Sonora, Mexico. Our key objective was to determine the value that GS can add to the current three-stage yield testing strategy at CIMMYT and we draw inferences from predictive modeling of GY using 420 different populations, environments, cycles and model combinations. First, we evaluated the potential of genomic predictions for minimizing the number of replications and lines tested within a site and year and obtained mean prediction accuracies (PAs) of 0.56, 0.5 and 0.42 in Stages 1,2 and 3 of yield testing, respectively. However, these PAs were similar to the mean pedigree-based PAs indicating that genomic relationships added no value to pedigree relationships in the yield testing stages, characterized by small family-sizes. Second, we evaluated genomic predictions for minimizing GY testing across stages/years in ObregonObregón and observed mean PAs of 0.41, 0.31 and 0.37, respectively when GY in the full irrigation bed planting (FI BP), drought stress (DS), and late-sown heat stress environments were predicted across years using genotype x environment (GxE) interaction models. Third, we evaluated genomic predictions for minimizing the number of yield testing environments and observed that in Stage 2, the FI BP, full irrigation flat planting and early-sown heat stress environments (mean PA of 0.37 + 0.12) and the reduced irrigation and DS environments (mean PA of 0.45 + 0.07) had moderate predictabilities among them. However, in both predictions across years and environments, the PAs were inconsistent across years and the GxE models had no advantage over the baseline model with environment and line effects. Overall, our results provide excellent insights into the predictability of a quantitative trait like GY and will have great important implications on the future design of GS for GY in wheat breeding programs globally.